Holistic Face Processing is Induced by Shape and Texture. (July 2013) - Meinhardt-Injac, Bozana; Persike, Malte; Meinhardt, Günter
There is increasing evidence that shape and texture are integral parts of face identity. However, it is less clear whether face-specific processing mechanisms are triggered by face shape alone, or if texture might play an important role. We address this question by studying mechanisms involved in holistic face processing. Face stimuli were either full-color pictures of real faces (shape and texture) or line drawings of the same faces (shape without texture). In a change detection task subjects judged whether eyes and eyebrows in two otherwise identical, sequentially presented faces were different in size or not. Afterwards, subjects had to identify the just presented face among two distractor faces (forced-choice identification task). The results obtained from the two tasks give rise to the conclusion that face identification and change detection tasks engage different processing strategies, which capture different aspects of holistic processing. Real faces were processed holistically, irrespective of task requirements, whereas line drawings were processed holistically only if face identification was required. On the basis of the data we conclude that face shape is relevant for the initial processing stage and feature binding, whereas face texture seems to be involved in processing of face configuration more specifically. Moreover, results demonstrate considerable flexibility of the face processing systems allowing for goal-directed and task-specific recall of face information.